2013
DOI: 10.4103/0972-5229.114825
|View full text |Cite
|
Sign up to set email alerts
|

Status epilepticus: An association with pyrethroid poisoning

Abstract: This report describes a 35 year old male who presented with seizures after consuming 4-5 bottles of “ALL-OUT” a commercial composition of pyrethroid used as insecticides. Our case report supports authors reporting an association of pyrethroid poisoning with status epilepticus.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
11
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 6 publications
0
11
0
Order By: Relevance
“…However, pyrethrins and pyrethroids are generally benign to mammals due to their negligible action on mammalian enzymes, as well as their lack of persistence in the environment 2. Generally, only a small body of literature describes human toxicity, which, when it does occur, is commonly a result of dermal exposure or intentional ingestion 3 4…”
Section: Discussionmentioning
confidence: 99%
“…However, pyrethrins and pyrethroids are generally benign to mammals due to their negligible action on mammalian enzymes, as well as their lack of persistence in the environment 2. Generally, only a small body of literature describes human toxicity, which, when it does occur, is commonly a result of dermal exposure or intentional ingestion 3 4…”
Section: Discussionmentioning
confidence: 99%
“…[1] along with literature support. The authors have also stressed that the practitioners shall consider this entity in the differential diagnosis of poisoning with seizures.…”
mentioning
confidence: 83%
“…Seizures following pyrethroid ingestion and its non-responsiveness to anticonvulsants were lamented by Panwar et al . [ 1 ] along with literature support. The authors have also stressed that the practitioners shall consider this entity in the differential diagnosis of poisoning with seizures.…”
mentioning
confidence: 88%
“…The efficacy and safety of a diet supplemented with a high-dose EPA and DHA (9 g/d added to 1 g/d ascorbic acid, 400UI/12 h α-tocopherol and 100 μg/d selenium) was assessed in patients with early-stage sepsis for 7 days. The investigators found patients had lower levels of CRP, IL-6 and procalcitonin, as well as less need for mechanical ventilation and reduced development of severe sepsis ( Hosny, Nahas, Ali, Elshafei, & Khaled, 2013 ). Evidence for beneficial effects of n-3 PUFA-containing diets in patients with severe ARDS demonstrated similar outcomes such as reduced duration of mechanical ventilation, shorter ICU length and improved oxygenation ( Langlois, D'Aragon, Hardy, & Manzanares, 2019 ).…”
Section: Role Of N-3 Polyunsaturated Fatty Acids In Patients With Resmentioning
confidence: 99%